2011
DOI: 10.1038/ki.2011.176
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular diseases associated with hematopoietic neoplasms: an expanding spectrum

Abstract: Once thought to be limited mainly to lesions involving deposition of monoclonal paraproteins, glomerular diseases associated with hematologic neoplasms now include forms in which manifestations are probably mediated through cytokines or chemokines. Said et al. studied one such lesion, myeloproliferative neoplasm-related glomerulopathy, and found it to be a late complication of these neoplasms, with a generally poor renal outcome. Whether earlier recognition of glomerular diseases associated with hematopoietic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(5 reference statements)
0
5
1
Order By: Relevance
“…Recently, Said et al (14) reported that MPNrelated glomerulopathy was a late complication of neoplasms with a generally poor renal outcome. Hass et al (15) questioned whether earlier recognition of MPN-related glomerulopathy might have resulted in better renal outcomes, yet evidence from other primary and secondary glomerular diseases suggests that this is not unreasonable. The present case did not exhibit either globally sclerotic glomeruli or moderate/severe tubulointerstitial scarring, which is different from the patients described by Said et al (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Said et al (14) reported that MPNrelated glomerulopathy was a late complication of neoplasms with a generally poor renal outcome. Hass et al (15) questioned whether earlier recognition of MPN-related glomerulopathy might have resulted in better renal outcomes, yet evidence from other primary and secondary glomerular diseases suggests that this is not unreasonable. The present case did not exhibit either globally sclerotic glomeruli or moderate/severe tubulointerstitial scarring, which is different from the patients described by Said et al (14).…”
Section: Discussionmentioning
confidence: 99%
“…Hematologic malignancies can lead to glomerular insults, such as matrix/abnormal protein accumulation, proliferative GN/hypercellular glomeruli, and podocytopathy (15). Plasma-cell dyscrasias, podocyte injury caused by neoplastic cells, and released cytokines/permeability factors might be causes of GN, but the exact mechanism is still unclear (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…However, no randomized-controlled study has been performed to evaluate the prevalence of renal alterations. To date, the most well-recognized and well-established associations with glomerular disorders have been in people with hematopoietic cancers [ 19 ] and solid tumor carcinomas [ 8 ]. One group has used a rat model (nude rat F344/NJcl-run) to study cancer related glomerulopathy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, immunotactoid glomerulopathy, cryoglobulinemic MPGN, amyloidosis, monoclonal immunoglobulin deposit disease and necrotizing pauci-immune crescentic glomerulonephritis have been described. [ 3 15 19 20 21 22 23 ] Autoimmune mechanisms and T-lymphocyte dysfunction are implicated in the pathogenesis. [ 20 ] In 5 patients of our series with NP range proteinuria, 3 had MPGN, 1 had FSGS and another 1 had DN.…”
Section: Discussionmentioning
confidence: 99%
“…Paraneoplastic glomerulopathies are increasingly recognized. [ 2 3 ] Most cases with renal function derangement respond to effective treatment of underlying neoplasm. The aim of this study was to compile clinical and histologic lesion of underlying malignancies, indication for biopsy, and characteristics of nephropathies.…”
Section: Introductionmentioning
confidence: 99%